(untitled) (Kinesiology, 2017)
The aim of this study was to compare how respiratory compensation point (RCP) and end-test power (EP) change in response to the same four-week high intensity interval training (HIIT). The power output associated with RCP and EP before and after HIIT were recorded in 24 recreationally active participants (14 men and 10 women). RCP was determined from an incremental exercise test and EP was derived from a three-minute maximal effort test on a cycle ergometer. A significant time (pretest/posttest) × measurement (EP/RCP) interaction was found (F(1, 23)=5.119, p<.05). Results from a paired-sample t-test indicated that both EP (t(23)= -5.221, p<.05) and RCP (t(23)=-3.049, p<.05) increased significantly from pretest to posttest. Furthermore, a small effect size (d=.36, 90%CI=[.13, .58]) was calculated for the pre/posttest changes in the examined thresholds indicating greater potential improvements in EP compared to RCP. The pre/posttest change in EP (mean=21 W, 90%CI=[14, 28 W]) exceeded its standard error of estimate (14 W), while RCP did not. Correlation analysis revealed that EP correlated with RCP at both pretest (r=.813, p<.05) and posttest (r=.873, p<.05), however, delta values between the two measures were not significantly related. Both EP and RCP can be used to assess the change of aerobic capacity after HIIT, but may be reflective of different physiological adaptations. Further, EP may be preferred over RCP when assessing the effects of HIIT. Key words: training, testing, physiology, fatigue